AN 8-YEAR-OLD CALIFORNIA GIRL WITH ASYMPTOMATIC HEPATIC CYSTS. Issue 7 (7th June 2022) - Passarelli, Patrick; Ramchandar, Nanda; Naheedy, John; Kling, Karen; Choi, Lillian; Pong, Alice
Abstract : Echinococcus infections are rare in the United States but may present a growing public health threat. We present the case of an 8-year-old female patient from Southern California who was diagnosed with hepatic echinococcosis after the incidental discovery of large hepatic cysts.